Saving Significant Amount of Time in MD Simulations by Using an Implicit Solvent Model and Elevated Temperatures. (7th March 2013) - Shub, Ifat; Schreiber, Ehud; Kliger, Yossef
Abstract : Molecular dynamic simulations are used for investigating various aspects of biological processes. Such simulations often require intensive computer power; therefore several solutions were developed to minimize the computer power needed, including the usage of elevated temperatures. Yet, such simulations are still not commonly used by the wide scientific community of chemists and biochemists. For about two years now, the molecular simulations suite GROMACS enables conducting simulations using implicit solvent models to further decrease runtimes. In order to quantify the saving in computer power, and to confirm the validity of the models, we followed the simple dissolution process of a single NaCl molecule. The results reveal approximately 350-fold decrease in real-world runtime when using an implicit solvent model and an elevated temperature, compared to using explicit water molecules and simulating at room temperature. In addition, in a wide range of temperatures, the dissolution times of NaCl are distributed, as expected, exponentially, both in explicit and in implicit solvent models, hence confirming the validity of the simulation approach. Hopefully, our findings will encourage many scientists to take advantage of the recent progress in the molecular dynamics field for various applications.